Peningkatan Keterampilan Menulis Puisi Dengan Media Gambar - Tsalitsatul Maulidah (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2020)
Writing learning activities, students still experience many difficulties because teachers use conventional learning methods. So that causes the interest and enthusiasm of students in learning to be less, and the results achieved are not optimal. With media in the form of images will make it easier for students to express their ideas. Therefore, this research aims to improve students' poetry writing skills by using picture media. Because media images can stimulate students to give imagination and make students creative in writing poetry. The research method used is qualitative. The subject of this research is grade V. The results of the study indicate that the ability to write poetry based on image media can improve students' poetry writing skills. Students can make poetry titles from predetermined themes, can choose new and creative words (diction), and can use speech. The creativity of students writing poetry uses two types of majors, and they are contrasting forms and comparison forms